(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Poberezhna N. O. The problem of modeling of educational process on the basis of information technologies. The article investigates the peculiarities of modeling educational process based on information technologies, the structure of curriculum and instructional kit is presented on the basis of information technologies.